(untitled) (Revista da Escola de Guerra Naval, 2024)
The Submarine Development Program (PROSUB), under management of the Brazilian Navy, has been developing naval nuclear propulsion technology and, for so, nuclear facilities for maritime activities. The objective of this paper is to present initial thoughts on an integrated approach for implementing the graded safeguards concept in the design of naval Nonreactor Nuclear Facilities (NRNFs) that support the Brazilian Nuclear Propulsion Program. The proposed Alternative is based on the concept of graded safeguards set forth by the United States Department of Energy (DOE). A regulatory framework has been proposed involving regulations from the International Atomic Energy Agency (IAEA), the DOE and the Brazilian National Nuclear Energy Commission (CNEN, Portuguese acronym). This gradual approach has the potential for a more affordable project, and thus the integrated safeguards approach inherent to DOE regulations presents itself as a viable option to complement CNEN NN 2.02 provisions regarding the design and licensing for naval NRNFs in Brazil.